2021
DOI: 10.1177/20503121211066150
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of self-monitoring of blood glucose among noninsulin-treated patients with type 2 diabetes in a primary care setting in Hong Kong: A cross-sectional study

Abstract: Objectives: The current study aimed to examine the relationship between patient characteristics (internal psychological, external psychological, internal physical, external physical, and educational) and self-monitoring of blood glucose among noninsulin-treated patients with type 2 diabetes in a local primary care setting. Methods: This was a cross-sectional study, in which data were collected by a structured questionnaire. Correlational and multivariate multiple regression analyses were performed. Three hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…T2DM patients with a life partner show better SMBG behavior than T2DM patients who do not have a life partner (Bonger et al, 2018;Mogre et al, 2017). A previous study shows that socioeconomic level determines SMBG behavior; higher education levels that show high socioeconomic status influence SMBG behavior (Bonger et al, 2018;Iwuala et al, 2015;Lv et al, 2021;Mak & Lau, 2021). Likewise, high-income levels indicate better SMBG behavior (Levine et al, 2009;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T2DM patients with a life partner show better SMBG behavior than T2DM patients who do not have a life partner (Bonger et al, 2018;Mogre et al, 2017). A previous study shows that socioeconomic level determines SMBG behavior; higher education levels that show high socioeconomic status influence SMBG behavior (Bonger et al, 2018;Iwuala et al, 2015;Lv et al, 2021;Mak & Lau, 2021). Likewise, high-income levels indicate better SMBG behavior (Levine et al, 2009;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as psychosocial factors, can also affect the behavior of people with T2DM, including hypoglycemic experiences, family motivation, and desire to see the effects of dietary changes. In addition, the desire to please doctors when approaching the appointment date is a factor that affects their adherence to SMBG (Mak & Lau, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were surprised to find that SMBG, as well as having a test for glycated hemoglobin, was also positively correlated with app usage frequency. Previous research has shown that patients who are successful at sticking to SMBG have higher levels of health-related knowledge, self-efficacy, and education (46), while all these factors work in favor of encouraging self-management of blood glucose (47,48).…”
Section: Basic Demographic Characteristicsmentioning
confidence: 99%